THE IMPLICATION OF INTERNATIONAL TRADE LIBERALIZATION TO THE PRODUCTION AND TRADE OF DOMESTIC FRUITS - Aldon M.H.P. Sinaga (Socio-Economics/Agribusiness Department, 2016)
Free trade, which is part of liberalization process upon international trade and the implementation of many trade agreements, already brought implication to domestic trade performance. The impact of free trade policy will affect to the trade management of domestic fruit. It can result in either negative or positive effects. The objective of this research was analyzing and studying responses of Indonesian local fruit trade performance in domestic market due to fluctuation change of fruit import as the result of free trade policy implementation. Data used in this research was secondary data. The data obtained from Department of Agriculture, Department of Industry and Trade, FAO, and Indonesian Central Bank database. That data was collected from 1980 to 2006. Model that created in this research was estimated by OLS (Ordinary Least Square) method. The results show that free trade implementation influences on increasing of imported quantity for apple, orange, banana, and papaya commodity, decreasing of total domestic fruit supply, decreasing of land area for mango, banana, orange, and papaya cultivation until its next 2 years period, decreasing of productivity for banana and papaya cultivation, and increasing of mango, banana, and papaya price in the farmer level until its next 2 years period.